Genetic variants in FBLIM1 gene do not contribute to SAPHO syndrome and chronic recurrent multifocal osteomyelitis in typical patient groups - Assmann, Gunter; Köhm, Michaela; Schuster, Volker; Behrens, Frank; Mössner, Rotraut; Magnolo, Nina; Oji, Vinzenz; Burkhardt, Harald; Hüffmeier, Ulrike (Bmc Medical Genetics, 2020)
BACKGROUND: Syndrome of synovitis acne pustulosis hyperostosis osteitis (SAPHO) and chronic recurrent multifocal osteomyelitis (CRMO) present two diseases of a dermatologic and rheumatologic spectrum that are variable in manifestation und therapeutic response. Genetic risk factors have long been assumed in both diseases, but no single reliable factor has been identified yet. Therefore, we aimed to clinically characterize a patient group with syndrome of synovitis acne pustulosis hyperostosis osteitis (SAPHO) (n = 47) and chronic recurrent multifocal osteomyelitis (CRMO)/ chronic non-bacterial osteomyelitis (CNO) (n = 9) and analyze a CRMO candidate gene. METHODS: Clinical data of all patients were collected and assessed for different combinations of clinical symptoms. SAPHO patients were grouped into categories according to the acronym; disease-contribution by pathogens was evaluated. We sequenced coding exons of FBLIM1. RESULTS: Palmoplantar pustular psoriasis (PPP) was the most common skin manifestation in CRMO/CNO and SAPHO patients; most SAPHO patients had sterno-costo-clavicular hyperostosis. The most common clinical category of the acronym was S_PHO (n = 26). Lack of pathogen detection from bone biopsies was more common than microbial isolation. We did not identify autosomal-recessive FBLIM1 variants. CONCLUSIONS: S_PHO is the most common combination of symptoms of its acronym. Genetic analyses of FBLIM1 did not provide evidence that this gene is relevant in our patient group. Our study indicates the need to elucidate SAPHO's and CRMO/CNO's pathogenesis.
CRIS-Team Scopus Importer:2020-05-22
Keywords: Association; Chronic non-bacterial osteomyelitis (CNO); Chronic recurrent multifocal osteomyelitis (CRMO); Coding variants; Syndrome of synovitis acne pustulosis hyperostosis osteitis (SAPHO (syndrome))